Tourism marketing mix of angke kapuk mangrove nature park as ecotourism - Nexen Alexandre Pinontoan; Willy Arafah; Nurbaeti Nurbaeti (Institute of Computer Science (IOCS), 2024)
The government's strategy in marketing ecotourism destinations is a crucial aspect of tourism development, particularly in collaboration with the management of Angke Kapuk Mangrove Nature Park to promote natural tourist spots through social media platforms. This research aims to investigate the Tourism Marketing Communication Strategy in promoting Angke Kapuk Mangrove Nature Park as an ecotourism destination. The researchers utilize the 7P marketing mix theory (Product, Price, Place, Promotion, People, Process & Physical Evidence), which facilitates practitioners on social media, particularly on Instagram. The research paradigm adopts a post-positivism approach, employing a qualitative method with descriptive analysis. The findings reveal that the management of Angke Kapuk Mangrove Nature Park has implemented effective strategies in promoting the destination through tourism marketing communication. This strategy includes promotional efforts featuring historical information, visually appealing content, and regular updates on social media. The research identifies certain challenges, such as a lack of public awareness about ecotourism. It is suggested that in the future, the management could enhance promotional activities accompanied by engaging tourism events. Success in marketing ecotourism destinations relies on providing comprehensive information to tourists, making them more familiar with religious tourism spots through social media or direct visits